2023
DOI: 10.3390/nu15081810
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation and Its Impact on Mortality and Cardiovascular Outcomes: Systematic Review and Meta-Analysis of 80 Randomized Clinical Trials

Abstract: Background: The impact of vitamin D supplementation on cardiovascular outcomes and mortality risk reduction remains unclear due to conflicting study findings. Methods: We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs), published between 1983 and 2022, that reported the effect of vitamin D supplementation in adults versus placebo or no treatment on all-cause mortality (ACM), cardiovascular mortality (CVM), non-cardiovascular mortality (non-CVM), and cardiovascular morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 119 publications
1
13
0
Order By: Relevance
“…This is similar to the results of our study, as the significant association was only with cardiac events but not overall SCVD or mortality. By contrast, in a Mendelian randomization analysis from the UK Biobank, a large-scale, prospective cohort from England, Scotland, and Wales, all-cause mortality increased by 25% for participants with a screening and management could be highly recommended to decrease CAD events attributed to it (26,27). Additionally, debate remains on the best tests for measuring vitamin D and recommended levels of vitamin D intake (28).…”
Section: Discussion:mentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the results of our study, as the significant association was only with cardiac events but not overall SCVD or mortality. By contrast, in a Mendelian randomization analysis from the UK Biobank, a large-scale, prospective cohort from England, Scotland, and Wales, all-cause mortality increased by 25% for participants with a screening and management could be highly recommended to decrease CAD events attributed to it (26,27). Additionally, debate remains on the best tests for measuring vitamin D and recommended levels of vitamin D intake (28).…”
Section: Discussion:mentioning
confidence: 99%
“…Although this study has a limitation of the lack of information on vitamin D supplementation, a recent Systematic Review and Meta-Analysis of 80 Randomized Clinical Trials found that vitamin D supplementation could reduce CVD events but not CVD or overall mortality. With vitamin D supplementation being recommended for more therapeutic and preventive justification and the high prevalence of vitamin D deficiency in the UAE and the region, its screening and management could be highly recommended to decrease CAD events attributed to it (26,27). Additionally, debate remains on the best tests for measuring vitamin D and recommended levels of vitamin D intake (28).…”
Section: Discussion:mentioning
confidence: 99%
“…In the VITAL study, supplementation with omega-3 fatty acids and vitamin D did not lessen the risk for cardiovascular events or cancer [13]. On the other hand, there are studies that have shown promising results, such as a possible link to decreased cancer incidence with MVM supplements [74] or supplementation with vitamin D linked with a lower risk of all-cause mortality [75]. Nevertheless, data are inadequate to recommend the use of DSs for the diminution of non-communicable diseases such as CVD events and cancer and all-cause mortality [12,76,77].…”
Section: Public Health Issues On Dietary Supplement (Ds) Intakementioning
confidence: 99%
“…25(OH)D deficiency has been linked to acute and chronic diseases that affect not only the skeletal system but also other physiological systems. Timely treatment for individuals with 25(OH)D deficiency can potentially improve their quality of life and reduce associated health risks 8…”
Section: Introductionmentioning
confidence: 99%
“…Timely treatment for individuals with 25(OH)D deficiency can potentially improve their quality of life and reduce associated health risks. 8 …”
Section: Introductionmentioning
confidence: 99%